Evaluating the cervical spine in confused or unconscious adults after blunt trauma. (2nd June 2019) - Deacon, Christopher; Craxford, Simon; Ollivere, Benjamin J
Abstract : Potential injury to the cervical spine should be considered in all patients who have suffered blunt trauma. Early spinal immobilization is required to minimize the risk of secondary spinal cord injury. However, prolonged immobilization is associated with its own morbidity. Clinical evaluation of the cervical spine in confused or unconscious adult trauma patients is challenging, and imaging is required to safely 'clear' the cervical spine. Despite the existence of national guidelines, significant variations in practice exist. This article summarizes the evidence for the initial stabilization of the cervical spine in adult trauma patients. It reviews the imaging modalities available and the criteria for discontinuation of cervical spine immobilization.